2022
DOI: 10.1038/s41420-022-00910-z
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemia-triggered ATF6-CHOP pathway aggravates acute inflammatory liver injury by β-catenin signaling

Abstract: Although hyperglycemia has been documented as an unfavorable element that can further induce liver ischemia–reperfusion injury (IRI), the related molecular mechanisms remain to be clearly elaborated. This study investigated the effective manner of endoplasmic reticulum (ER) stress signaling in hyperglycemia-exacerbated liver IRI. Here we demonstrated that in the liver tissues and Kupffer cells (KCs) of DM patients and STZ-induced hyperglycemic mice, the ER stress-ATF6-CHOP signaling pathway is activated. TLR4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…Autophagy signaling pathways of both ATF-4 and CHOP recorded a significant reduction in their expression upon LPS intoxication. Consistent with our findings, it was demonstrated that hyperglycemia triggered ATF–CHOP signaling pathways upon LPS intoxication that it may promote pro-inflammatory response in macrophages [ 65 ].…”
Section: Discussionsupporting
confidence: 91%
“…Autophagy signaling pathways of both ATF-4 and CHOP recorded a significant reduction in their expression upon LPS intoxication. Consistent with our findings, it was demonstrated that hyperglycemia triggered ATF–CHOP signaling pathways upon LPS intoxication that it may promote pro-inflammatory response in macrophages [ 65 ].…”
Section: Discussionsupporting
confidence: 91%
“…This axis is a critical regulator of stimulators of interferon genes/tank binding kinase 1 (STING/TBK1) mediated immune response and also mediated apoptotic pathways in IR stress liver injury [ 65 ]. Hyperglycemia triggers ER stress, thereby activates ATF6-CHOP pathways and inhibits β-catenin, causing deteriorating liver in hepatic IRI [ 66 ].…”
Section: Er Stress Response In Liver Diseasesmentioning
confidence: 99%
“…Among these, it is well accepted that excessive inflammatory responses and oxidative stress are the most important factor in the occurrence and process of ALI. Patients with ALI exhibited higher levels of proinflammatory cytokines (TNF-α, IL-1β, and IL-6), lower levels of anti-inflammatory cytokines (IL-10), and lower activities of antioxidative enzymes (total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), and catalase (CAT)) [ 4 ]. Therefore, inhibition of inflammatory responses and oxidative stress is considered an effective approach for the treatment of ALI.…”
Section: Introductionmentioning
confidence: 99%